2013
DOI: 10.1155/2013/915490
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Temporal and Cross-National Poverty and Mortality Rates among Developed Countries

Abstract: A prime objective of welfare state activities is to take action to enhance population health and to decrease mortality risks. For several centuries, poverty has been seen as a key social risk factor in these respects. Consequently, the fight against poverty has historically been at the forefront of public health and social policy. The relationship between relative poverty rates and population health indicators is less self-evident, notwithstanding the obvious similarity to the debated topic of the relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 32 publications
3
17
0
Order By: Relevance
“…The evidence here relates to a body of literature that shows the importance of poverty also in the richer world (Ludwig et al, 2011(Ludwig et al, , 2012Fritzell et al, 2013), and suggests that, in order to improve health and ameliorate social ills, raising the living standard is still a crucial task in the more affluent countries, not just in the poorer ones as Wilkinson and Pickett (2009) suggest. Poverty still matters, and sometimes it matters more than inequality.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The evidence here relates to a body of literature that shows the importance of poverty also in the richer world (Ludwig et al, 2011(Ludwig et al, , 2012Fritzell et al, 2013), and suggests that, in order to improve health and ameliorate social ills, raising the living standard is still a crucial task in the more affluent countries, not just in the poorer ones as Wilkinson and Pickett (2009) suggest. Poverty still matters, and sometimes it matters more than inequality.…”
Section: Discussionmentioning
confidence: 65%
“…At a different level of analysis, Fritzell et al (2013) look at the role of relative poverty over time across 26 countries (affluent countries and some post-socialist Eastern European countries), and find that poverty has a detrimental effect on death risk also in affluent countries.…”
Section: Income Inequality and Health: Evidence And Debatementioning
confidence: 99%
“…Earlier research suggests that in affluent countries, the level of relative poverty seems important for mortality (Fritzell et al 2013). In this study, in addition to relative poverty, we used a fixed poverty rate -the American poverty threshold -to examine the association between poverty and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…We study the cross-temporal and cross-national relationship between poverty rates and mortality rates in 30 nations. Findings from earlier research comparing the consequences of poverty in affluent countries have indeed suggested that relative poverty is associated with mortality rates (Fritzell et al 2013).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation